Determinant of Behavioral Intention to Use E-wedding Gifts - Ranti Mawardi; Yulia Hendri Yeni; Vera Pujani (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
This study aims to analyze the effect of perceived risk, perceived ease of use, and customer's attitude on behavioral intention to use e-wedding gifts in Padang. The type of research is explanatory research, with the research method being a descriptive survey that emphasizes quantitative methods. The sample is 160 users and those who intend to use the e-wedding gift in the city of Padang. The sampling technique is purposive sampling. The data analysis method used Structural Equation Modeling - Partial Least Square (SEM-PLS). The results showed that perceived risk had a significant effect on perceived ease of use, perceived risk had a significant impact on customer attitude, perceived risk had no significant effect on behavioral intention to use, perceived ease of use had no significant effect on behavioral intention to use, and customer attitude has a significant impact. The behavioral choice to use and perceived risk significantly affect behavioral intention to use through customer attitude. This study has several significant findings for e-wedding gift providers. The researcher hopes that this research can be developed so that the use of e-wedding gifts as the adoption of banking technology and digital wallets for alternative wedding gifts can be implemented better.